COLLABORATIVE GOVERNANCE IN MEDICAL PROFESSION REGULATION: LESSONS LEARNT FROM INDONESIA - Titi Savitri Prihatiningsih (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Medical profession regulation are carried out through certification and licensure which can be executed by the government, the organizational profession or the collaboration of both. Having a long standing credibility in professional regulation, medical professions have required every medical graduate to undergo certification and licensure process. The UK system adopts the government-led and the USA system has opted for the professional-led medical regulation. In Indonesia currently there are two laws regulating medical profession, namely Medical Practice Law No.29/2004 and Medical Education Law. No.20/2013. These two Laws have given mandates for medical profession regulation to different stakeholders, resulting in conflicting roles and functions, particularly in certification and licensure. Attempts to overcome these situations have been initiated, by inviting all stakeholders involved to discuss the solution during the period of December 2014-January 2015. This study aims at understanding the decision making process to achieve consensus using the concept of collaborative governance.Method: Qualitative method using a case study is applied and documents analysis is used for data collection. Thematic analysis is employed for data analysis.Results: Six themes are identified to reflect the decision making process in collaborative governance. It starts with distrust, followed by mutual understanding and willingness to listen, then common goals are agreed. Each stakeholder conducts an internal reflection and eventually accepts a consensus.Conclusion: The concept of collaborative governance can be applied in medical profession regulation to achieve consensus in collective decision making process.